Compressive behavior and microstructural properties of tailings polypropylene fibre-reinforced cemented paste backfill. (30th November 2018) - Chen, Xin; Shi, Xiuzhi; Zhou, Jian; Chen, Qiusong; Li, Enming; Du, Xianghong
Graphical abstract: Highlights: PP fibre can improve the UCS, stiffness, ductility and stability of CPB. Best fibre parameter levels are a fibre content of 0.15% and a fibre length of 6 mm. PP fibre bring much more improvement to the early strength of CPB. Fibre can bridge the cracks of CPB. Abstract: This experimental study was carried out to investigate the influence of polypropylene (PP) fibre on the compressive behavior and microstructural properties of tailings (classified as CL – lean clay) cemented paste backfill (CPB). The compressive behavior was determined by the unconfined compressive strength (UCS), and structural changes in CPB were evaluated by macrostructural failure analysis and microstructural tests with scanning electron microscopy (SEM) analysis. Orthogonal tests were designed to research the influences and significance of the cement content, solid mass concentration, fibre content and fibre length on CPB. The results indicate that although the fibre parameters are not as significant as the cement content and solid mass concentration for CPB strength, they are also important factors for improving the UCS of CPB, and the effect of PP fibre on the early (3 days curing time) and later (28 days curing time) stage strength of the backfill is much more obvious than that on the medium stage (7 days curing time) strength. And fibre can enhance the stiffness and ductility of CPB with increasing strain and E 50 . In addition, the fibre content is much more important than the fibre length, there is no linear relationship between UCS and the fibre parameters (fibre content and fibre length), and the best fibre parameter levels are a fibre content of 0.15% and a fibre length of 6 mm in this study. Moreover, macrostructural failure analysis and SEM microstructural tests indicated that PP fibre tend to bridge the cracks, which can reduce the porosity of the CPB matrix and improve its compactness, integrity and residual strength with some calcium silicate hydrate (C-S-H) gelling trapped on its surface.